CanCOG®: cultural adaptation of the evidence-based UCLA cognitive rehabilitation intervention program for cancer survivors in Portugal - Oliveira, Ana F. (2023)
Cognitive difficulties are highly prevalent and negatively impact cancer survivors' quality of life. The UCLA Cognitive Rehabilitation Intervention Program (in short, UCLA program) is an evidence-based intervention developed and tested in the US to address the cognitive complaints of cancer survivors. Since there are no cognitive rehabilitation programs available for Portuguese cancer-related settings, this study aimed to culturally adapt the UCLA program to Portugal. Nine steps were implemented for this cultural adaptation: needs assessment, initial contacts, translation, cultural adaptation, independent review by a panel of experts (n = 6), focus group discussions with cancer survivors (n = 11), systematization of inputs and improvement of the final materials, fidelity check, and preliminary acceptability assessment. The findings suggested that changes to the original materials were needed. A Portuguese name, "CanCOG®-Reabilitação Cognitiva no Cancro" (in English "CanCOG®-Cognitive Rehabilitation in Cancer"), and a logo were created to make it more memorable and appealing for the Portuguese population. The language was adjusted to ensure content accessibility and semantic and conceptual equivalence. Finally, references to several cultural aspects, such as habits, customs, and traditions, were adapted to fit the new cultural context. The UCLA program may be a promising tool to help alleviate the cognitive difficulties reported by cancer survivors in different cultural contexts. Future research is needed to confirm the feasibility, acceptability, and preliminary efficacy of its Portuguese version, "CanCOG®-Reabilitação Cognitiva no Cancro".